Nutritional Potential of Tenebrio molitor Larvae Produced from Organic Waste Bioconversion as an Alternative Feed Ingredient: Evaluation Against Indonesian National Feed Standards For Broiler, Layer, and Fish Feedstock - Muhammad Gibran Al-Ghafari; Praditya Sigit Ardisty Sitogasa; Muhammad Faisal Fadhil; Rossyda Priyadarsini; Aulia Ulfah Farahdiba (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The increasing demand for sustainable protein sources and the accumulation of organic waste have encouraged the development of insect-mediated bioconversion for resource recovery. This study evaluated the nutritional quality of Tenebrio molitor larvae reared on various organic waste substrates and assessed their suitability as an alternative feed ingredient in accordance with the Indonesian National Standards (SNI). A laboratory-scale factorial experiment was conducted using three substrate treatments: household food waste (S1), a 1:1 mixture of household food waste and seafood waste (S2), and seafood waste (S3), combined with two larval densities (0.5 and 1 larva cm?²). Harvested larvae were analyzed for crude protein, crude fat, moisture, ash, and carbohydrate contents, and data were evaluated using two-way ANOVA. Substrate composition, larval density, and their interaction significantly affected all proximate parameters (p < 0.001). The highest crude protein content (37.16%) was obtained from larvae reared on seafood waste at 1 larva cm?² (S3-D1), while carbohydrate content decreased with increasing seafood waste proportions. Crude fat ranged from 24.80–27.14%, moisture from 10.10–12.25%, and ash from 9.60–10.73%. The larvae met SNI requirements for protein and moisture in broiler, layer, and tilapia feeds. These findings demonstrate that T. molitor effectively converts organic waste into protein-rich biomass, supporting its application as a sustainable feed ingredient and promoting circular resource management. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible ConsumptionSDG 13: Climate ActionSDG 15: Life on Land